mpact of Collaborative Learning on Student`s Academic Performancein Teacher’sEducation Program (Journal of Asian Development Studies, 2024)
Creating a classroomenvironmentfor learners to participate actively and engage is an integral element of a comprehensive educational initiative for actively learning students in higher education institutions.Students collaborate to attain goals through collaborativelearning. The idea behind collaborativelearningis that students may help each other learn and build a deeper comprehension of the subject matter by working together. The study examines the influence ofcollaborativelearningon the academicperformanceof students at B.Ed.Levelsfocusingon social factors such as interaction with peers, interaction with teachers, and social media usage influenceCL and collaborativelearningto improve the student's academicperformance.Social constructivism theorywas usedto observe student performance. Data havebeen collectedthrough questionnaires from four private universities.Findings were evaluatedthrough SPSS version 22;the composite reliability of the instrument was measuredas α=0.954. Theresults of the regression analysis confirmed and accepted all three hypotheses.Itcan be concludedthat all three independent variables-studentinteraction with peers, interaction with teachers, and social media use-positivelyimpact collaborativelearningandhelp students improve their academicperformanceand achieve their goals. The results of this study suggest that collaborativelearningisan effectiveapproach to enhancing academicPerformancein higher education (B.Ed. Honors) and that social factors play animportantrole in promoting collaboration among students. The findings have implications for teaching and learning practices in higher education, where collaborativelearningmay be especially beneficial. Overall, this research highlights the importance ofcollaborativelearningin promoting academic development in students.